2017
DOI: 10.5380/cep.v35i1.55932
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantification of Fatty Acids in Chia Seeds Produced in Brazil

Abstract: Chia is a good source of fi bre, protein and antioxidants, and is also rich in polyunsaturated fatty acids, particularly α-linolenic acid (18:3 n-3). This fact makes it increasingly interesting for studies of its composition and nutritional quality, because it may be useful for inclusion in diets or in novel food formulations. The objective of this study was to determine the chemical and fatty acid composition and the indices of nutritional quality of the lipid fraction of chia seed produced in Brazil. In resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
2
5
0
Order By: Relevance
“…These values agreed very well with the data reported for marine fish, where AI = 0.26-0.60 and TI = 0.20-0.44 (42). Chia (AI = 0.09, TI = 0.05) and flax seeds (AI = 0.06, TI = 71.7) presented lower AI and TI, except for a much higher TI in flax seeds (40,41).…”
Section: Indexes Of Lipid Nutritional Quality (Inq)supporting
confidence: 90%
See 2 more Smart Citations
“…These values agreed very well with the data reported for marine fish, where AI = 0.26-0.60 and TI = 0.20-0.44 (42). Chia (AI = 0.09, TI = 0.05) and flax seeds (AI = 0.06, TI = 71.7) presented lower AI and TI, except for a much higher TI in flax seeds (40,41).…”
Section: Indexes Of Lipid Nutritional Quality (Inq)supporting
confidence: 90%
“…Alver and LG- Chlorella had even higher H/H values of 4.5 and 3.7, respectively. The H/H values in microalgae were lower compared to that of chia (H/H = 11.4) or flax seeds (H/H = 17.3) ( 40 , 41 ). When compared to marine fish (H/H = 0.9–2.5), the analyzed microalgal biomass had an excellent H/H ratio ( 42 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…A higher yield of chia seed oil was obtained using the Soxhlet apparatus and a mixture of ethers similar to those described previously using petroleum ether [10], as compared to the chloroform and methanol mixture used in the Folch-based procedure [8]. Nevertheless, oil yields with both methods ranged between 29% and 35%, which are comparable to those values provided by the EU commission (between 30% and 35%, [5]).…”
Section: Discussionsupporting
confidence: 76%
“…Both the seeds and oil are EU-approved for consumption [4][5][6], and studies have highlighted their prophylactic properties for metabolic syndrome, hypertension, and cardiovascular diseases. Studies of the composition of chia seeds revealed a content of around 65% ALA of total fat, and up to 20% of linoleic acid [2,[7][8][9][10]. In addition, chia seed oil also contains antioxidants [2,7,[10][11][12], which could also contribute to the interest of this product in nutrition and health.…”
Section: Introductionmentioning
confidence: 99%